Selective Nutrient Transport in Bacteria: Multicomponent Transporter Systems Reign Supreme - Davies, James S.; Currie, Michael J.; Wright, Joshua D.; Newton-Vesty, Michael C.; North, Rachel A.; Mace, Peter D.; Allison, Jane R.; Dobson, Renwick C.J. (Frontiers in Molecular Biosciences, 2021)
Multicomponent transporters are used by bacteria to transport a wide range of nutrients. These systems use a substrate-binding protein to bind the nutrient with high affinity and then deliver it to a membrane-bound transporter for uptake. Nutrient uptake pathways are linked to the colonisation potential and pathogenicity of bacteria in humans and, as such, may be candidates for antimicrobial targeting. Here we review current research into bacterial multicomponent transport systems, with an emphasis on the interaction at the membrane, as well as new perspectives on the role of lipids and higher oligomers in these complex systems.